Konstruksi Sosial Pemerintahan Desa Terhadap Pengembangan Ekonomi Kampung Turis Desa Licin, Kabupaten Banyuwangi - Juliana Bulan Pertiwi; Rizky Trisna Putri; Dewien Nabielah Agustin (Jurnal Pariwisata dan Budaya, 2026)
The development of a tourist village in Licin Village demonstrates interesting social dynamics, as tourism growth is influenced not only by the potential of the Ijen Crater but also by how the community interprets and collectively builds an economic system. The minimal formal role of the village government in homestay management has led residents to build their own economic structure based on cooperation, equity, and solidarity. This social understanding is a crucial factor in the success of the tourism economy in Licin Village. This research used a qualitative method with Berger & Luckmann's social construction approach. Data analysis was conducted through three stages of social construction: externalization, objectivation, and internalization. The results indicate the formation of a social reality that develops through the community's social processes. First, the community constructs the tourism system as a joint venture that must be managed fairly and equitably. Second, work structures such as the homestay rotation system, role allocation, and village supervision become objective rules accepted as normal. Third, the values ​​of solidarity, income distribution, and service ethics are ultimately internalized as the identity of the tourism village residents. Thus, the social construction of the Licin Village community forms a community-based tourism management model capable of maintaining social harmony and village economic sustainability.